PENGARUH PEMBERIAN TEH DAUN TIN (Ficus Carica) DOSIS DUA KALI SEHARI TERHADAP KADAR TOTAL KOLESTEROL PADA MAHASISWA OBESITAS DI POLTEKKES RS dr. SOEPRAOEN MALANG - Bayu Budi Laksono; Mokhtar Jamil (Jurnal Kesehatan Mesencephalon, 2018)
Hypercholesterolemia is a condition when cholesterol levels exceed normal range. Hypercolesterolemia  associated with an increased risk of cardio vascular diseases such as Acute Coronary Syndromes (ACS) and Cerebro Vascullar Accident. It is estimated that more than 6 million people suffer from hypercholesterolemia worldwide. College students are a population at risk of suffering from hypercholesterolemia due to an irregular lifestyle accompanied by a lack of physical activity. Tin leaf (Ficus Carica) tea can be used to control cholesterol levels. This research used Quasi experiment design with Repeated measurement (pretest and posttest) design approach. Research Sample were 23 students with obesity who were divided into 2 groups  Repeated ANOVA analysis show there are significant differences between groups (p = 0.017). Bonferoni Post Hoc analysis shows that there are significant differences between Pretest and post test data in the first week (p = o.011). Flavonoids and pectin in the tin leaf (Ficus carica) play an important role in cholesterol regulation. Flavonoids can increase the expression of HDL-C (good cholesterol), whereas pectin increases the secretion of sterols in Cecal metabolism. Consumption of  twice daily tin leave tea  was proven in reduce blood cholesterol levels in respondents. It can be conclude there were significant differences of total cholesterol levels before treatment, 1 week after and 2 weeks after administration of Tin (ficus carica)  tea  leaf with a dose twice a day in Obese College students at the Poltekkes Rumah sakit dr. Soepraoen Malang. Key Words: Cholesterol, College Student, Obesity,Tin (ficus carica)